1981
DOI: 10.1002/bit.260230224
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia excretion by Azotobacter chroococcum

Abstract: The increasing cost of petroleum products required in nitrogen fertilizer production has focused attention on the development of biological systems for nitrogen fixation. One approach used is the enhancement of N2 fixation in free living microorganisms. The isolation of nifderepressed auxotrophic mutants of Klebsiella pneumoniae' and the derepressed control mutants of Azotobacter vinelandii* suggested the possibility of using such mutants for the fermentative production of ammonia. The recent report of Wallace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…These results are in accordance with our previous study on cotton, where the use of half dose of mineral NPK with effective microorganisms (EM)þorganic matter (OM) saves mineral N fertilizer by almost 50% compared to a system with only mineral NPK application (Khaliq et al 2006). The increases in yield and yield attributes due to the application of biofertilizer supplemented with organic and chemical N fertilizer may be explained by mechanisms of N 2 fixation (Lakshminarayana et al, 1992), ammonia excretion (Narula et al 1980), phosphate solubilization (Kundu and Gaur 1980), and growth hormone production (Azcon and Barea 1976). For example, the Azotobacter culture used in biofertilizers is reported as a producer of several plant hormones, such as gibberellic acid, indole 3-acetic acid (IAA), and cytokinin, that promote growth and yield of a crop (Barea and Brown 1974;Kızılkaya 2008).…”
Section: Yield and Yield Attributessupporting
confidence: 93%
“…These results are in accordance with our previous study on cotton, where the use of half dose of mineral NPK with effective microorganisms (EM)þorganic matter (OM) saves mineral N fertilizer by almost 50% compared to a system with only mineral NPK application (Khaliq et al 2006). The increases in yield and yield attributes due to the application of biofertilizer supplemented with organic and chemical N fertilizer may be explained by mechanisms of N 2 fixation (Lakshminarayana et al, 1992), ammonia excretion (Narula et al 1980), phosphate solubilization (Kundu and Gaur 1980), and growth hormone production (Azcon and Barea 1976). For example, the Azotobacter culture used in biofertilizers is reported as a producer of several plant hormones, such as gibberellic acid, indole 3-acetic acid (IAA), and cytokinin, that promote growth and yield of a crop (Barea and Brown 1974;Kızılkaya 2008).…”
Section: Yield and Yield Attributessupporting
confidence: 93%
“…Ammonia is the immediate product of nitrogen fixation in nitrogen fixing micro-organisms. Narula et al, (1981) and Chandna (1982) reported that wild strains of A. chroococcum are able to release ammonia in medium containing 1% sucrose as a carbon source. Lakshaminarayana et al, (2000) reported that diazotroph like Azotobacter had good capability of conversion of nitrogen to ammonia.…”
Section: Resultsmentioning
confidence: 99%
“…Besides nitrogen fixation, Azotobacter synthesises and secretes considerable amount of biologically active substances like B-vitamins, nicotinic acids, pentothenic acids, biotin, heteroauxins, gibberellins, etc., which are reported to enhance the growth of plants and their tolerance to pathogenic diseases (Van Loon 2007). Various crops in India have been inoculated with diazotrophs, especially Azotobacter spp., which excretes ammonia in the rhizosphere in presence of root exudates and helps in modification of nutrient uptake by the plants (Narula et al 1981). Moreover, for sustainable soil fertility, blending of the chemical fertilisers with chemical-adoptive strains is one approach that may derive synergistic benefits for balancing the physico-chemical and biological properties (Vargas et al 2000).…”
Section: Introductionmentioning
confidence: 99%